IN VITRO ASSESSMENT OF ANTIUROLITHIATIC ACTIVITY OF APIGENIN WITH NITRIC ALGINATE VARIATION IN NANOSUSPENSION - Neneng Nasliah; Suci Nurainun; Ghina Annufus; Audy Nursifa'atun; Aufalya Wibirezkina; Sofi Nurmay Stiani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Kidney stones are hard kidney material, such as stones that originate from minerals and salts. Alternative therapy using medicinal plants as anticalculi is an option for treating kidney stones. One plant with anticalculi activity is celery, which contains various active chemical compounds, including apigenin. Apigenin is a diuretic that can help the kidneys remove excess fluid and salt from the body. However, apigenin has low solubility in water. To overcome the limited solubility of apigenin, nanosuspensions were prepared. This study aimed to formulate a nanosuspension, evaluate its preparation, and test it in vitro. This formula uses the concentration of the suspending agent, Na. The different alginates were F0 without active substances (0%) and F1 (1%), F2 (2%), and F3 (3%). The evaluation of the preparation includes tests for pH, viscosity, specific gravity, particle size, zeta potential, and adsorption efficiency. The results showed that the preparation had an average pH value of 4-7, an average viscosity value of 78-162 cP, a specific gravity of 0.98-1.02 g/mL, the preparation had a particle size of 928–974 nm, zeta potential of-26, 3 to -41.7, and an average entrapment efficiency of 99.63%-99.64%. Apigenin nanosuspension preparations can dissolve kidney stone calcium at 1800-7800 ppm. The test results showed that the apigenin nanosuspension has the potential to dissolve calcium kidney stones. Keywords: kidney stones, apigenin, in vitro, nanosuspension